1979
DOI: 10.1073/pnas.76.5.2199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cibacron blue F3GA on oligonucleotide binding site of estradiol--receptor complexes of mouse uterine cytosol.

Abstract: It is believed that steroid hormones induce differential gene expression in target cells by combining with specific cytoplasmic receptor proteins that subsequently translocate to the nuclear compartment where they interact with a limited number of acceptor sites (1). Although the nature of these nuclear acceptor sites is still unclear, it is well established that almost all steroid receptors described are able to combine with DNA (2-4). Andre and Rochefort (5) have demonstrated that the affinity of the estradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This sulfonated polyaromatic dye is thought to interact with the "dinucleotide fold" of DNA-binding proteins. It has been reported to inhibit DNA-cellulose binding of estrogen receptor (131), and DNA-cellulose, phosphocellulose, and ADP-Sepharose binding of androgen receptor (120). In our laboratory, we have found that the inhibitor's effects on native progesterone receptor aggregates resembles, at least grossly, those of pyridoxal phosphate: it dissociates them without causing transformation, at least as monitored by in vitro DNA binding ( /.…”
Section: Othersmentioning
confidence: 84%
See 1 more Smart Citation
“…This sulfonated polyaromatic dye is thought to interact with the "dinucleotide fold" of DNA-binding proteins. It has been reported to inhibit DNA-cellulose binding of estrogen receptor (131), and DNA-cellulose, phosphocellulose, and ADP-Sepharose binding of androgen receptor (120). In our laboratory, we have found that the inhibitor's effects on native progesterone receptor aggregates resembles, at least grossly, those of pyridoxal phosphate: it dissociates them without causing transformation, at least as monitored by in vitro DNA binding ( /.…”
Section: Othersmentioning
confidence: 84%
“…This makes it a most interesting inhibitor, worthy of further study. An inhibition of binding of hormone to receptor has also been reported for this agent (131,132).…”
Section: Othersmentioning
confidence: 89%
“…The extent of binding to oligo(dT) followed the order: In prior experiments the mouse uterine cytosol E2R binding affinity for oligo(dG)-cellulose was the most stable after exposure to inhibitors of DNA binding [ 10,16,17]. Also binding to oligo(dT)-cellulose was usually more stable than oligo(dC)-cellulose interactions.…”
Section: Ehrsmentioning
confidence: 94%
“…Testosterone was included at 1.2 pM to saturate nonestradiol binding sites. Unbound estradiol was separated from macromolecule-bound steroid with charcoal dextran as previously described [ 10,13,14]. In a parallel incubation a 200-fold excess of unlabeled estradiol was included.…”
Section: Preparation Of [3h]estradiol Receptor Complexes (E2r)mentioning
confidence: 99%
“…[7,8] These effects arise from the structural similarities between CB (see structure in Scheme 1) and both naturally occurring heterocycles (for example, NAD + , coenzyme A and folic acid) [8] and nucleotides. [8][9][10] CB and other anthraquinone dyes are generally called 'biomimetic dyes' or 'nucleotide-mimetic ligands' because of the specificity of their interaction with the nucleotide binding sites of several enzymes and proteins that have been shown to bind nucleotide substrates. [11,12] These types of dyes essentially mimic the structure of adenine nucleotides, such as ATP, ADP, NAD and NADH.…”
Section: Introductionmentioning
confidence: 99%